Research progress of early biomarkers of hyperuricemia-induced renal injury - Zeng Chui-ke; Li Bing (Linchuang shenzangbing zazhi, 2025)
Hyperuricemia （HUA）-induced kidney injury has an insidious early onset and usually does not show clinical symptoms. Clinical indicators such as creatinine and urea nitrogen lack sensitivity and specificity in detecting early decline in kidney function， which are often detected only when the glomerular filtration rate falls to half of the healthy level. At this time point， the kidney may have irreversible damage. Therefore， the search for early biomarkers associated with HUA-induced kidney injury is crucial for clinical intervention and prognosis. This article reviewed the research progress on the mechanism and early biomarkers of HUA-induced kidney injury.